ANALYSIS OF LEUKOCYTE TYPES IN TUBERCULOSIS PATIENTS UNDERGOING TREATMENT WITH ANTI-TUBERCULOSIS DRUGS (OAT) IN BENGKULU CITY - Baruara, Guntur; Iqoranny Susilo, Avrilya (Politeknik Kesehatan Kemenkes Bengkulu, 2024)
Tuberculosis is a disease in Indonesia that has received special attention from the Ministry of Health. Tuberculosis is a deadly infectious infectious disease, this is because Mycobacterium Tuberculosis has infected the world's population. Transmission of tuberculosis can be through droplets during coughing or sneezing and can infect other healthy people. Tuberculosis patients receive routine treatment with Anti-Tuberculosis Drugs. In the process, this drug has an effect on the number of leukocytes which previously increased in number due to infection and the presence of antibodies that bind to the leukocyte cell membrane causing lysis of leukocyte cells. Checking the number of leukocytes is useful as a diagnostic basis because it can describe the occurrence and process of the disease in the body of tuberculosis patients. The purpose of this study is to describe the characteristics of tuberculosis patients based on gender and age, describe the type of leukocytes of patients who received anti-tuberculosis drug treatment during the May-July 2024 period in the Bengkulu City area. In this study, a research design with a cross sectional descriptive method was used to see the characteristics of leukocytes during tuberculosis patients receiving treatment with anti-tuberculosis drugs. The samples used were tuberculosis patients who were receiving anti-tuberculosis drug treatment in the work area of the Nusa Indah Health Center, Bengkulu City. Patients will have their blood samples taken for analysis of their leukocytes without looking at the identity of the treatment period. The results of the count of basophils, eosinophils, rod neutrophils and monocytes showed normal values, while the results of the count of segment neutrophils, lymphocytes, leukocytes were found in some patients with abnormal values. This is possible because the anti-tuberculosis drugs taken can reduce the number of leukocytes that increase at the time of infection and in some patients are abnormal because it is still in the early stages of treatment.